Analysis Of The Application Of Learning Media By Teachers To Improve Literacy In High School Students In Central Java - Urip Widodo; Walyono Walyono; Mugiyo Mugiyo; Subandi Agus; Justin Farrell (Universitas Negeri Malang, 2025)
The rapid development of information technology in Indonesia requires teenagers to have good digital literacy in order to be able to use technology wisely and productively. Adequate digital literacy will help adolescents access information critically, maintain privacy, and participate actively and safely in the digital world. This research method uses interviews and surveys to collect data from the high school student population in Central Java, which allows researchers to obtain in-depth information about students' views and experiences. The sample taken in Banjarnegara Regency will provide a representative picture that helps researchers analyze trends and patterns among high school students in the region. The study results showed that the habit of reading has not been formed from an early age in children, so they tend not to like reading activities. Another thing that encourages children is that the lack of reading habits at home and the surrounding environment makes children less interested in books and unaware of the benefits and pleasures that can be obtained from reading. Students will prefer to read in a supportive environment, such as a home that provides a lot of books and parents who regularly read stories. The interview results show several ways to attract and motivate to increase reading interest, including integrating literacy into the school curriculum, teaching children how to search for information online, organizing extracurricular literacy activities, and teaching children how to organize and manage information. Good material that meets the needs of students will help develop an interest in reading and writing and strengthen the ability to analyze and understand the text as a whole; literacy is at the forefront of society in tackling fake news.The literacy culture still needs to be developed. Therefore, cooperation from all parties, including the government, schools, and the community, is needed to build awareness of the importance of reading and increase access to literary sources.